KARAKTERISTIK SISTEM PARLEMENTER DALAM SISTEM PEMERINTAHAN DI INDONESIA PASCA AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - IZZATI, HALIMAH NUR; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Enforcement of the governance system of a country can be affected by various factors, based on the needs, historical factors and socio-political conditions of a country. To know a country's system of government is to see the mission of the Constitution of each country, whether the country is embracing parliamentary system of government (parliamentary system) or the presidential system of government (presidential system). Parliamentary system is a system that emphasizes the parliament as a subject of the government, while the presidential system emphasizes the role of executive president as the subject of government.Completion of the system of government after the amendment of the Constitution of the Republic of Indonesia Year 1945 in order to truly meet the basic principles of the presidential system has been attempted, such as the strengthening of several articles of the Constitution of the Republic of Indonesia Year 1945 as the mechanism of impeachment of a president who governed more detailed and procedural again. However there are still some phenomena in the life of the state is likely to lead to parliamentary. It's like when the position of the House is getting stronger or a majority of parliamentarians are not the opposition party or parties supporting the President, then the President can not be completely ruled as much about strategic policies that must be taken with the House according to the provisions contained in Act Constitution of the Republic of Indonesia Year 1945.key words: system of government - a parliamentary government system characteristics - Act of 1945